Correction: Estimating the cooperativity of PROTAC-induced ternary complexes using 19F NMR displacement assay. Issue 1 (20th December 2021) - de Castro, Guilherme Vieira; Ciulli, Alessio
Abstract : Correction for 'Estimating the cooperativity of PROTAC-induced ternary complexes using 19 F NMR displacement assay' by Guilherme Vieira de Castro et al., RSC Med. Chem., 2021, 12, 1765–1770, DOI: ; 10.1039/D1MD00215E .